Analysis of Mitochondrial Dimensions and Cristae Structure in Pluripotent Stem Cells Using Transmission Electron Microscopy. (10th October 2018) - Tobias, I. C.; Khazaee, R.; Betts, D. H.
Abstract: Dynamic alterations to mitochondrial structure and function regulate cell fate decisions and underlie multiple age‐related and genetic diseases that are modeled using embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs). Transmission electron microscopy (TEM) can be used to obtain high‐resolution micrographs of mitochondria, but mitochondrial ultrastructure is easily distorted during specimen processing. This unit describes a method that preserves mitochondrial membrane structure from adherent ESC cultures for TEM sample preparation. This procedure is useful for assessing ultrastructural changes to mitochondria during differentiation, reprogramming, or experimental manipulation of ESC metabolism. We provide comprehensive protocols for: (1) preparation of ESC cultures for TEM; (2) retrieval of thin sections from individual ESCs; and (3) contrast staining and morphometric analysis of mitochondria and cristae. This unit also describes an alternative procedure for samples with low cell numbers and a supporting protocol for morphometric image analysis. Collectively, these protocols allow for the observation and quantitative analysis of mitochondria in ESCs. © 2018 by John Wiley & Sons, Inc.